The Effectiveness of the Duolingo Application in Learning English Vocabulary for High School Students - Silalahi, Dumaris E; Purba, Igna Mariana; Sirait, Eka Uchi Monica; Panjaitan, Anita; Zamorano, Alex (English Education Department at FKIP Nommensen University, 2025)
The use of learning media is one of the important things in the era of increasingly rapid technological development. It makes learning interesting and effective. An effective English language and teaching media in this new era is Duolingo. It provides methods of learning while playing games, which certainly attracts the attention of language learners. The effective use of Duolingo application is described based on the result of pretest and posttest comparison. The research method is quantitative based on the participants’ scores. The test is vocabulary test which addressed into the students of class XII SMA N 1 PERUMNAS BATU 6 as the participants. Data analysis indicate that Duolingo application is an effective English language and teaching media. The average score in pretes is 64. 53 and it becomes 91.13. This research concluded that Dulingo help the participants to improve English vocabulary knowledge.